Remuneration of Ex-Offico Board Members in Zambia: Governance Implications & Policy Perspectives (African Journal of Public Administration & Management, 2026)
Develop clear written policies on ex- officio roles and compensation.Prefer non-monetary (training, awards) recognitionAllow compensation only additional duties are provenAlign with King IV, OECD, and emerging Zambian Code. 4th December 2025Strengthen role of Board Secretaries as governance custodians.
Keywords: Remunerations; Governance Implications & Policy Perspectives; Ex-Offico Board Members